2005
DOI: 10.1111/j.1744-9987.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinal Sodium‐dependent Inorganic Phosphate Transport by Fibroblast Growth Factor 23

Abstract: The mechanisms by which fibroblast growth factor 23 (FGF23) alters inorganic phosphate (Pi) homeostasis is not entirely clear. In the present study, we examined the effect of FGF23 on intestinal sodium-dependent Pi transport in mice. Injection of FGF23(R179Q) markedly reduced serum Pi and 1,25(OH)2D3 levels in normal mice. Those animals show the reduction of intestinal sodium-dependent Pi transport activity and the amount of type IIb sodium-dependent Pi cotransporter (type IIb NaPi) protein in the brush border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 20 publications
3
73
0
3
Order By: Relevance
“…Using BBM vesicles, FGF-23 was previously shown to affect intestinal phosphate absorption; however, a regional effect has not been described. 13 Interestingly, our previous studies demonstrated that although there are striking differences in the regional profile of phosphate handling by the rat and mouse small intestine, in both rodent species, only the jejunum shows an increase in phosphate absorption in response to 1,25(OH) 2 D 3 . 6 This finding, together with the results of this study, suggests that the jejunum, at least in the rat, is of particular importance in the regulation of phosphate absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using BBM vesicles, FGF-23 was previously shown to affect intestinal phosphate absorption; however, a regional effect has not been described. 13 Interestingly, our previous studies demonstrated that although there are striking differences in the regional profile of phosphate handling by the rat and mouse small intestine, in both rodent species, only the jejunum shows an increase in phosphate absorption in response to 1,25(OH) 2 D 3 . 6 This finding, together with the results of this study, suggests that the jejunum, at least in the rat, is of particular importance in the regulation of phosphate absorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that FGF-23 injection into normal mice causes a reduction in plasma 1,25(OH) 2 D 3 with concomitant inhibition of intestinal (using BBM vesicles) phosphate transport and NaPi-IIb protein expression. 13 Moreover, injection of FGF-23 into vitamin D receptor (VDR) null mice does not elicit any change in intestinal phosphate transport activity or in transporter expression, indicating that the action of FGF-23 depends on the VDR. 13 Conversely, administration of 1,25(OH) 2 D 3 to mice results in a dramatic increase in serum FGF-23 levels, and it has been proposed that these two hormones are part of a kidneyintestine-bone axis that controls phosphate balance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when examined in mice, the effect of FGF-23 to suppress intestinal NaPi2b protein was vitamin D receptor dependent. 16 The net effect of PO4 loading on 1,25 (OH) 2 D in healthy humans is difficult to predict because hyperphosphatemia and increased FGF-23 were demonstrated to inhibit while increased PTH was shown to stimulate 1a-hydroxylase. [17][18][19] In addition, FGF-23 is positively regulated by 1,25(OH) 2 D, PTH, and Klotho.…”
mentioning
confidence: 99%
“…In XLH, a loss-of-function mutation in PHEX leads to a decrease in Fa, resulting in an increase in FGF23a and the resultant renal phosphate wasting and inappropriately low 1,25(OH) 2 D levels. (55); therefore, it is not surprising that standard or even high doses of vitamin D had little effect on serum phosphorus and produced only small changes in urinary phosphate excretion in W.M. With megadoses of vitamin D (1,500,000 U/d), serum calcium rose, whereas serum phosphorus was unchanged (Figure 1).…”
Section: Other Potential Phosphatonin/minhibins In Xlhmentioning
confidence: 99%